2021
DOI: 10.3390/nu13061950
|View full text |Cite
|
Sign up to set email alerts
|

Matcha Green Tea Alleviates Non-Alcoholic Fatty Liver Disease in High-Fat Diet-Induced Obese Mice by Regulating Lipid Metabolism and Inflammatory Responses

Abstract: Lately, matcha green tea has gained popularity as a beverage and food additive. It has proved to be effective in preventing obesity and related metabolic syndromes. However, the underlying mechanisms of its control effects against non-alcoholic fatty liver disease (NAFLD) are complicated and remain elusive. In the present study, we performed an in vivo experiment using male C57BL/6 mice fed with a high-fat diet and simultaneously treated with matcha for six weeks. Serum biochemical parameters, histological cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…Some studies have reported that matcha has hypolipidemic, hypoglycemic, and anti-obesity effects ( 11 , 12 ). Consistently, our previous study focused on liver function and found that matcha was effective in improving HFD-induced hepatitis and lipid metabolism disorders ( 13 ). However, the interactions between multiple organs and the clear mechanisms of matcha on HFD-induced obesity remained to be further explored.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Some studies have reported that matcha has hypolipidemic, hypoglycemic, and anti-obesity effects ( 11 , 12 ). Consistently, our previous study focused on liver function and found that matcha was effective in improving HFD-induced hepatitis and lipid metabolism disorders ( 13 ). However, the interactions between multiple organs and the clear mechanisms of matcha on HFD-induced obesity remained to be further explored.…”
Section: Introductionsupporting
confidence: 70%
“…The composition of experimental diets is shown in Supplementary Table S1 . The normal chow diet (10% energy from fat, #D12450B) and high-fat diet (45% energy from fat, #D12451) for mice were supplied by the Research Diets, Inc. Co., Ltd. (New Brunswick, NJ, USA) ( 13 ). The body weight and food intake of each group of mice were measured weekly.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, the visceral adipose mass of obese mice and lean littermates fed with diets containing 1 or 2% green tea extract was significantly lower than their respective controls fed with a green tea extractfree diet (25). In another study, an HFD significantly increased the weight of epididymal and perirenal adipose tissues, and the size of adipocytes in mice, while the dietary supplement Matcha prevented these unfavorable changes (26). Likewise, Selenium-Enriched Matcha (GT9) and Seven Star Matcha (GT10) in this study could reduce the accumulation of adipose and the hypertrophy of adipocytes.…”
Section: Effects Of Green Teas On Visceral Adipose Tissuementioning
confidence: 88%
“…NAFLD is recognized as a multisystem pathological disease, and its clinical development is closely associated with metabolic syndromes, including hypertension, hyperlipidemia and diabetes mellitus [ 39 ]. Although early-stage NAFLD hardly causes immediate damage, accumulating evidence has shown that a severe form of NAFLD accompanied by hepatic and extrahepatic complications is highly related to elevated hepatic inflammatory responses [ 40 ]. On the other hand, the increased uptake of free fatty acids and triglycerides from circulation and their dysregulated hepatic accumulation play a central role in the progression of NAFLD to NASH [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%